2016
DOI: 10.5530/srp.2017.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Indian Plants with Cardioprotective Activity – A Review

Abstract: Cardio-protection includes" all mechanism and means that contribute to the preservation of the heart by reducing or even preventing Myocardial damage. Cardiovascular disease (CVD) remains the principle cause of death in both developed and developing countries. It may present as a typical heart attack, a sudden death or it may be detected at an advanced stage and be described as a silent infarct. CVD includes high blood pressure, coronary heart disease, congestive heart failure, stroke and accounts Myocardial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Biofilm production activity was scored visually comparing the thickness of adherent layer as strong(+++), moderate (++), weak (+) and negative (-). These results correlate with a study by [43] who reported that carrier strains of S. aureus and more other nasal transport strains shape biofilms. This critical concern in nasal colonization for the reason that several biofilm-producing strains of S. aureus effect of antibiotics 500 times the level active versus free-floating planktonic cells, they may form biofilms to overcome the natural antimicrobials in host's nasal mucosaand the clearance mechanisms produced by host and synthetic sources.…”
Section: Biofilm Production: Tube Methodsupporting
confidence: 91%
See 1 more Smart Citation
“…Biofilm production activity was scored visually comparing the thickness of adherent layer as strong(+++), moderate (++), weak (+) and negative (-). These results correlate with a study by [43] who reported that carrier strains of S. aureus and more other nasal transport strains shape biofilms. This critical concern in nasal colonization for the reason that several biofilm-producing strains of S. aureus effect of antibiotics 500 times the level active versus free-floating planktonic cells, they may form biofilms to overcome the natural antimicrobials in host's nasal mucosaand the clearance mechanisms produced by host and synthetic sources.…”
Section: Biofilm Production: Tube Methodsupporting
confidence: 91%
“…In a study on Bacillus subtilis, biofilm formation was elevated under the influence of biocide ClO2, and it was explained as a self-capable to protect the environment [48]. The dosage of plant extract is a definitive agent in biofilm suppression and using the suitable a quantity of plant extracts may be given an adverse outcome, i.e., extra biofilm production [43].Moreover, these findingsindicate that antimicrobial plants could also potentially possess antipathogenic activities, which may not be related to growth inhibition of the microorganism [49]. Microtiter assay was more efficient in demonstrating effective eradication of biofilm produced by all Staphylococcus isolates used in the current study.…”
Section: Antibiofilm Activity Of Essential Oils: Tube Methodmentioning
confidence: 99%
“…With this in mind, focused research on natural products of herbal origin with negligible side effects to explore their cardioprotective potential came into being ( Allawadhi et al, 2018 ; Shah et al, 2019 ). Over the years, several plants like Amaranthus viridis , Ginkgo biloba , Terminalia arjuna , Tinospora cordifolia , Curcuma longa , Hydrocotyle asiatica , Centella asiatica , Allium sativum , Withania somnifera , Garcinia kola, Zingiber officinale, and many others have been assessed for their cardioprotective potential ( Shah et al, 2019 ; Kumar et al, 2017 ). Some of the plant-derived bioactive compounds with potent cardioprotective activity include digoxin (arrhythmia treatment), atropine (bradycardia treatment), allicin, kolaviron, caffeic acid, epigallocatechin-3-gallate, resveratrol, carotenoids, with their therapeutic activities like potent antioxidant anti-hypertensive, anti-atherosclerotic, anti-inflammatory, and improving insulin sensitivity properties to name a few ( Shah et al, 2019 ; Sharifi-Rad et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of many important modern drugs has the starting point as natural products. ThePotential source of drugs as a medicinalplant because there were rich in secondary metabolites and essential oil of therapeutic medicines [5]. Medicinal plants were used in various ailments are due to being economical, effective, their ease availability and due to their safety [5].…”
Section: Introductionmentioning
confidence: 99%
“…ThePotential source of drugs as a medicinalplant because there were rich in secondary metabolites and essential oil of therapeutic medicines [5]. Medicinal plants were used in various ailments are due to being economical, effective, their ease availability and due to their safety [5]. Because of these advantages the usage of medicinal plant were increased by the medicinal practitioners in their day to day practice [6].…”
Section: Introductionmentioning
confidence: 99%